1980
DOI: 10.2135/cropsci1980.0011183x002000010015x
|View full text |Cite
|
Sign up to set email alerts
|

Collection and Evaluation of Avena Fatua for Use in Oat Improvement1

Abstract: More than 2,200 samples of the wild oat (Avena fatua L.) were collected from western North Central U.S. as part of a program to preserve natural variant populations of this species and to further evaluate its potential as a germplasm source for the improvement of cultivated oats (A. sativa L.). This report summarizes the results of screening these samples for tolerance to barley yellow dwarf virus (BYDV), resistance to cereal leaf beetle (Oulema melanopus L.), and resistance to oat stem rust (Puccinia graminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…W . Rines and noted as `previously selected as BYDV-resistant' were included in the 1981 and 1982 trials (RINEs et al ., 1980) . Their BYDV resistance was generally confirmed, but no BYDV-resistant A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…W . Rines and noted as `previously selected as BYDV-resistant' were included in the 1981 and 1982 trials (RINEs et al ., 1980) . Their BYDV resistance was generally confirmed, but no BYDV-resistant A .…”
Section: Resultsmentioning
confidence: 99%
“…2 Selected by H . Jedlinski from Rine's collections(RINES et al ., 1980) . 3 Selected by the author(COMEAU, 1982) .°BAUM (1977) considers some tetraploids may belong to A .…”
mentioning
confidence: 99%
“…The studies of RINES et al (1980), ROBBINS et al (1977), and REICH & BRINKMAN (1984) indicate that A. @uu has higher groat protein percentage than A. s&vu.…”
Section: Introductionmentioning
confidence: 94%
“…RINES et al (1980) identified tolerance to the cereal leafbeetle (Oulemu melunopus L.) and to barley yellow dwarf virus in a small percentage of A. futuu genotypes. B. STEVENS REICH & BRINKMAN, 1984;RINES et al, 1980), resistance to both of these rusts has been reported in A. fatua genotypes from California, Texas and Mexico (ATKINS et al, 1966;ROBBINS et al, 1971). f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Using molecular markers, Barbosa-Neto (1995) identified a number of chromosome regions associated to BYDV tolerance varying from two to eight, according the environment were phenotypic evaluation was carried out. Good tolerance sources were found in other oat species, including hexaploids A. sterilis L. and A. fatua, and diploid A. strigosa Schreber (Comeau, 1982;Rines et al, 1980;Jedlinsky, 1983).…”
Section: Resistance × × Tolerancementioning
confidence: 99%